The importance of specific IgE antibodies in the epidemiology of allergic rhinitis and asthma (ECAP survey): part four. The relationship between the concentration of specific IgE antibodies in serum and types of asthma - Namysłowski, Andrzej; Lipiec, Agnieszka; Zieliński, Wojciech; Raciborski, Filip; Krzych-Fałta, Edyta; Samoliński, Krzysztof; Szylling, Anna; Samoliński, Bolesław (Postȩpy dermatologii i alergologii, 2023)
Specific immunoglobulins E (sIgE) are important parameters for the estimation of severity of allergic diseases.IntroductionSpecific immunoglobulins E (sIgE) are important parameters for the estimation of severity of allergic diseases.To determine the relationship between the concentration of specific IgE antibodies in serum and types of asthma.AimTo determine the relationship between the concentration of specific IgE antibodies in serum and types of asthma.The concentration of sIgE antibodies against allergens Dermatophagoides pteronyssinus, cat dander, timothy grass, and Alternaria alternata were determined in the serum of 4077 respondents randomly selected from 8 regions (ECAP study). The positive results of sIgE (≥ 0.35 IU/ml or ≥ 0.7 IU/ml) were correlated to clinical diagnosis (types of asthma, skin-prick tests).Material and methodsThe concentration of sIgE antibodies against allergens Dermatophagoides pteronyssinus, cat dander, timothy grass, and Alternaria alternata were determined in the serum of 4077 respondents randomly selected from 8 regions (ECAP study). The positive results of sIgE (≥ 0.35 IU/ml or ≥ 0.7 IU/ml) were correlated to clinical diagnosis (types of asthma, skin-prick tests).sIgE antibodies against any allergen were detected in 9.9% (classes 1-6)/7.6% (classes 2-6) of healthy respondents. Comparing sIgE antibodies of respondents with intermittent asthma to sIgE antibodies of respondents with persistent asthma, no statistically significant differences were identified. Relating to allergens of D. pteronyssinus, cat dander, and A. alternata, sIgE antibodies were more frequently detected in respondents with atopic asthma and a negative skin-prick test as compared to healthy respondents with a negative skin-prick test (p < 0.005 to p < 0.001). Relating to allergens of D. pteronyssinus, cat dander, and timothy grass, sIgE antibodies were more frequently detected in respondents with atopic asthma and a weakly positive skin-prick test as compared to healthy respondents with weakly positive skin-prick test (p < 0.05 to p < 0.001).ResultssIgE antibodies against any allergen were detected in 9.9% (classes 1-6)/7.6% (classes 2-6) of healthy respondents. Comparing sIgE antibodies of respondents with intermittent asthma to sIgE antibodies of respondents with persistent asthma, no statistically significant differences were identified. Relating to allergens of D. pteronyssinus, cat dander, and A. alternata, sIgE antibodies were more frequently detected in respondents with atopic asthma and a negative skin-prick test as compared to healthy respondents with a negative skin-prick test (p < 0.005 to p < 0.001). Relating to allergens of D. pteronyssinus, cat dander, and timothy grass, sIgE antibodies were more frequently detected in respondents with atopic asthma and a weakly positive skin-prick test as compared to healthy respondents with weakly positive skin-prick test (p < 0.05 to p < 0.001).Regarding subjects with a negative or weakly positive skin test, when sIgE antibodies to the same allergen are detected, asthma is much more likely to occur.ConclusionsRegarding subjects with a negative or weakly positive skin test, when sIgE antibodies to the same allergen are detected, asthma is much more likely to occur.